1980
DOI: 10.1002/jclp.6120360205
|View full text |Cite
|
Sign up to set email alerts
|

The social interest index: A study of construct validity

Abstract: Investigated the construct validity of the Social Interest Index (SII) on a sample (N = 140) of hospitalized male alcoholics. Because of the inferred properties of social interest, it was hypothesized that the SII would relate positively with measures of some social traits, mental health, intelligence, education, and internal locus of control and would relate negatively with measures of other social traits and MMPI "pathology" scales. The hypotheses generally were supported. The significant positive correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…First, the results indicated that social interest was a significant predictor of health status as measured by the three health indices. Although previous researchers found a positive relationship between social interest and life adjustment (Crandall & Lehman, 1977;Crandall & Putnam, 1980;Mozdzierz & Semyck, 1980;Zarski et al, 1981), the findings of this study extended this context to include health-related variables. Specifically, the results indicated that social interest is consistently associated with high overall health, a low number of somatic symptoms, and high energy level.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…First, the results indicated that social interest was a significant predictor of health status as measured by the three health indices. Although previous researchers found a positive relationship between social interest and life adjustment (Crandall & Lehman, 1977;Crandall & Putnam, 1980;Mozdzierz & Semyck, 1980;Zarski et al, 1981), the findings of this study extended this context to include health-related variables. Specifically, the results indicated that social interest is consistently associated with high overall health, a low number of somatic symptoms, and high energy level.…”
Section: Discussionmentioning
confidence: 50%
“…Because previous stress research has been hampered by psychometric limitations, including the use of theoretically incompatible variables (Moracco & McFadden, 1982;Stensrud & Stensrud, 1983), it was necessary to select a variable consistent with Lazarus's model. On the basis of findings relevant to Lazarus's model that point to social interest as a psychosocial characteristic mediating the stress-life adjustment outcome (Crandall & Kytonen, 1980;Crandall & Lehman, 1977) and on increasing evidence that supports Adler's views on the relationship between social interest and adjustment (Crandall & Putnam, 1980;Hjelle, 1975;Mozdzierz & Semyck, 1980;Zarski et al, 1981), we determined that social interest was an appropriate and compatible research variable.…”
mentioning
confidence: 99%
“…Greever et al (1973) reported an internal reliability coefficient of .81 and a test-retest reliability coefficient of .79 for the total SII. Support for the concurrent validity of the SII (Bubenzer, Zarski, & Walter, 1979;Hjelle, 1975;Kaplan, 1978) and the construct validity (Mozdzierz & Semyck, 1980) also has been reported. In order to utilize the data for a factor analysis, the SII was modified in form.…”
Section: Instrumentsmentioning
confidence: 94%
“…Previous research regarding social interest, sex, and age is limited and warrants further exploration. For example, Mozdzierz and Semyck (1980) found a negative relationship between age and the SII in a male pathological sample. Greever, Tseng, and Friedland (1973), however, found a positive relationship between SII and age for females but not for males.…”
mentioning
confidence: 98%
See 1 more Smart Citation